Pengaruh Pendidikan Islam Nonformal Pimpinan Ranting Aisyiyah (Pra) Pabelan Terhadap Perkembangan Akhlak Jama'ah Tahun 2017(Studi Kasus Ibu-ibu Jama'ah Pengajian Ahad Pagi Masjid Al-Kautsar Dusun Mendungan) - , Efiana, Drs. M. Darojat Ariyanto, M.Ag (2017)
Islamic education is an education that includes physical and mental educations in which the sources of the teaching are al-Qur'ān and Sunnah. Islamic education is very important to be received by society, either from formal, non formal or informal institutions. In addition to renew the religious knowledge, by the presence of Islamic education, it is hoped that it can regulate the daily behavior in order to be appropriate to the Islamic law, in which the behavior is often called as akhlak (morality). Akhlak is a condition or character owned by an individual signified by the occurence of many kinds of actions done spontaneously without being prepared and does not need any thought first. One of institutions that is still exists in developing the activities of non formal Islamic education is Pimpinan Ranting Aisyiyah (PRA/The Branch Leadership of Aisyiyah) of Pabelan in which one of their activities is Sunday moring proselytizing. The problem statement in this research is whether there is an influnce of the non formal Islamic Education of Pimpinan Ranting Aisyiyah (PRA) of Pabelan on the development of akhlak of the congregation in 2017. Objects of this research are female congregation of the Sunday morning proselytizing in Al-Kautsar Mosque in Mendungan. Type of this research is a field research through a quantitative research. The methods of data collection used are interview, documentation, observation and questionnaire. The purpose of this research is to know whether the non formal Islamic education held by the Pimpinan Ranting Aisyiyah (PRA) of Pabelan can influence the development of behavior of the female congregation of the Sunday morning proselytizing in Al-Kautsar Mosque of Mendungan in 2017. Based on the results of the research conducted, it can be concluded that there is an influence from the Islamic education held by the PRA of Pabelan on the development of akhlak of the proselytizing congregation with medium and sufficient levels of correlation, therefore, the alternative hypothesis is accepted and the null hypothesis is rejected.